2022
DOI: 10.1101/2022.08.11.503682
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association analysis of hyperspectral reflectance data to dissect growth-related traits genetic architecture in maize under inoculation with plant growth-promoting bacteria

Abstract: Plant growth-promoting bacteria (PGPB) may be of use for increasing crop yield and plant resilience to biotic and abiotic stressors. Using hyperspectral reflectance data to assess growth-related traits may shed light on the underlying genetics as such data can help assess biochemical and physiological traits. This study aimed to integrate hyperspectral reflectance data with genome-wide association analyses to examine maize growth-related traits under PGPB inoculation. A total of 360 inbred maize lines with 13,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…These GWAS revealed a highly polygenic architecture of response to PGPB, with the identification of multiple Quantitative Trait Loci (QTLs) with small effects. The fine mapping of these QTLs revealed candidate genes involved in plant immunity (Kamfwa et al, 2015;Vidotti et al, 2019;Yassue et al, 2023), hormonal pathways (Vidotti et al, 2019;Cotta et al, 2020;Plucani do Amaral et al, 2023), nutrient uptake and provision (Stanton-Geddes et al, 2013;Curtin et al, 2017;Torkamaneh et al, 2020;Plucani do Amaral et al, 2023;Yassue et al, 2023) and plant development (Wintermans et al, 2016;Cotta et al, 2020), which is in line with the main pathways identified by analysis of mutants affecting microbiota structure in plants (Bergelson et al, 2021).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…These GWAS revealed a highly polygenic architecture of response to PGPB, with the identification of multiple Quantitative Trait Loci (QTLs) with small effects. The fine mapping of these QTLs revealed candidate genes involved in plant immunity (Kamfwa et al, 2015;Vidotti et al, 2019;Yassue et al, 2023), hormonal pathways (Vidotti et al, 2019;Cotta et al, 2020;Plucani do Amaral et al, 2023), nutrient uptake and provision (Stanton-Geddes et al, 2013;Curtin et al, 2017;Torkamaneh et al, 2020;Plucani do Amaral et al, 2023;Yassue et al, 2023) and plant development (Wintermans et al, 2016;Cotta et al, 2020), which is in line with the main pathways identified by analysis of mutants affecting microbiota structure in plants (Bergelson et al, 2021).…”
Section: Introductionsupporting
confidence: 60%
“…This requires the identification of host genetic factors either by using artificial genetic variation or by exploiting natural genetic variation (Bergelson et al, 2021). The latter approach was adopted by setting up genome-wide association studies (GWAS) on diverse plants including the model plants Arabidopsis thaliana (Wintermans et al, 2016;Cotta et al, 2020;Plucani do Amaral et al, 2023) and Medicago truncatula (Stanton-Geddes et al, 2013) as well as diverse crops such as maize (Vidotti et al, 2019;Yassue et al, 2021;Yassue et al, 2023), soybean (Torkamaneh et al, 2020) and common bean (Kamfwa et al, 2015). These GWAS revealed a highly polygenic architecture of response to PGPB, with the identification of multiple Quantitative Trait Loci (QTLs) with small effects.…”
Section: Introductionmentioning
confidence: 99%